Assessing the determinants of cloud computing adoption: An analysis of the manufacturing and services sectors - Oliveira, Tiago; Thomas, Manoj; Espadanal, Mariana (Information & management, 2014)
Many factors influence the adoption of cloud computing. Organizations must systematically evaluate these factors before deciding to adopt cloud-based solutions. To assess the determinants that influence the adoption of cloud computing, we develop a research model based on the innovation characteristics from the diffusion of innovation (DOI) theory and the technology-organization-environment (TOE) framework. Data collected from 369 firms in Portugal are used to test the related hypotheses. The study also investigates the determinants of cloud-computing adoption in the manufacturing and services sectors.